Analisis Sistem Antrean Layanan Jasa Antar Online pada Mahasiswa Pendidikan Matematika Universitas Jember - Zahra, Safinaz (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The rapid growth of app-based food delivery services has increased their usage, particularly among college students, leading to issues related to wait times and service efficiency. This study aims to analyze the queueing model and system performance of app-based food delivery services. This study involved 258 mathematics education students at the University of Jember as respondents. Distribution was determined using the Kolmogorov–Smirnov test; the model was determined using Kendall’s notation, and system performance was evaluated using the Allen–Cunneen approximation approach. The resulting queueing system model is M/G/3:FIFO/∞/∞. The results show that the system utilization rate is very low, namely 4,923242 × 10^−3 (GoFood), 5,809648 × 10^−3 (GrabFood), and 6,865131 × 10^−3 (ShopeeFood), indicating that the system is in a stable state. The values of Lq and Wq are close to zero, specifically 1,73634 × 10^−9 and 1,72427 × 10^−9 for A, 3,46587 × 10^−9 and 3,24824 × 10^−9 at B, and 6,98997 × 10^−9 and 6,35451 × 10^−9 at C, indicating that customers experience almost no service delay. Based on these results, the queuing system under study has operated efficiently and stably; however, there is a trade-off between cost efficiency and service quality in determining the optimal number of servers
Finalisasi oleh Agus 14 Juli 2026
Keywords: Queuing Theory; Online Food Delivery Service; System Performance; Cost Simulation